Effect of pedestal fan use on serum stress biomarkers in older adults exposed to simulated daylong indoor overheating - Ben J. Lee; Thomas McCarthy; Fergus O'Connor; Sarah L. Davey; C. Douglas Thake; James J. McCormick; Kelli E. King; Pierre Boulay; Robert D. Meade; Glen P. Kenny (Physiological Reports)
Abstract There is an urgent need to develop targeted heat‐alleviation strategies to protect heat‐vulnerable older adults. We have shown that electric fan use had nominal impact on reducing body core temperature and cardiovascular strain during daylong exposure to simulated indoor overheating. Here, we examined the effects of pedestal fan use during exposure to hot conditions on systemic markers of enterocyte damage, immune activation, renal ischemia, and inflammation in older adults. Eighteen adults (8 females; age 72, SD 7 years) underwent 3 randomized 8‐h exposures to 36°C, 45% relative humidity seated in front of a fan delivering air speeds of 0 m/s (control), 2 m/s (normal air speed delivered by electric fans), or 4 m/s (air speed used in biophysical modeling). Body core temperature and cardiovascular strain were measured throughout. Blood samples were obtained for analysis of systemic biomarkers before and at the end of exposure. End‐exposure core temperature was elevated ~1.0°C from baseline in all conditions. Following heat exposure, IFABP increased by 364 pg/mL [95% CI: 59, 670; p = 0.02] and LBP increased by 3.06 ng/mL [1.12, 5.00; p = 0.002] but was not different between the fan use and control condition (all p ≥ 0.15). No changes were observed for sCD14, IL‐6, TNFα, CRP, or NGAL (all p ≥ 0.15). The use of electric fans during daylong exposure to indoor overheating failed to meaningfully mitigate increases in physiological strain or biochemical markers associated with enterocyte damage and immune activation in older adults. ClinicalTrials.gov identifier: NCT05695079.